2019
DOI: 10.21603/2308-4057-2019-1-131-142
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of important processing conditions for rice bran sourdough fermentation using Lactobacillus plantarum

Abstract: The potentials of rice bran sourdough in bread making are recently gaining popularity. However, there is no information on the influence of processing conditions on the quality attributes of rice bran sourdough. To inves- tigate the influence of fermentation time and temperature on the levels of acidity (pH and TTA) in rice bran sour- dough fermented with L. plantarum, we applied response surface methodology (RSM). Furthermore, we studied the effect of different fermentation time and temperature on the total p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Faster acidification as the temperature increased from 28 °C to 35 °C was also reported in [ 20 ]. Similar to the present findings, Bolarinwa et al [ 21 ] reported that fermentation time and temperature were significantly affected by pH change and the acidification rate, which increased as the fermentation temperature increased. The fast dough acidification in type-2 fermentation at higher temperatures could be beneficial for industrial applications, such as inhibiting the growth of spontaneous, naturally occurring yeasts [ 22 ].…”
Section: Resultssupporting
confidence: 91%
“…Faster acidification as the temperature increased from 28 °C to 35 °C was also reported in [ 20 ]. Similar to the present findings, Bolarinwa et al [ 21 ] reported that fermentation time and temperature were significantly affected by pH change and the acidification rate, which increased as the fermentation temperature increased. The fast dough acidification in type-2 fermentation at higher temperatures could be beneficial for industrial applications, such as inhibiting the growth of spontaneous, naturally occurring yeasts [ 22 ].…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, wholegrain flour still contained more protein and enzymes that exhibit a buffering effect [ 23 ]. Bolarinwa et al [ 11 ] investigated the influence of temperature and fermentation time on pH and TTA by creating a prediction model using response surface methodology. In comparison, we varied temperature and flour types to increase the variance for the calibration input and then examined the prediction performance for our target variables.…”
Section: Discussionmentioning
confidence: 99%
“…Grote et al [ 10 ] used fluorescence spectroscopy to monitor the sourdough fermentation process online. In the study by Bolarinwa et al [ 11 ], the influence of processing conditions on the levels of pH and TTA was determined in rice sourdough. They developed a prediction model that could predict the response of pH and TTA.…”
Section: Introductionmentioning
confidence: 99%
“…Application of sourdough fermentation technology in bread enriched with rice bran resulted in increased loaf volume, phenolic content and consumer acceptance [188]. In another study, incorporation of sourdough from bran in bread making resulted in bread with an appealing aroma and a longer shelf-life [189].…”
Section: Valorisation Of Cereal By-products Through New Product Develmentioning
confidence: 97%